Off With Their Assists: An Empirical Study of Driving Skill in Forza Motorsports 4 - Debeauvais, Thomas; Zimmermann, Tom; Nagappan, Nachi; Carter, Kevin; Cooper, Ryan; Greenawalt, Dan; Solberg, Tyson (Proceedings of the 9th International Conference on the Foundations of Digital Games (FDG 2014), 2014)
This paper describes patterns of skill progression in Forza Motorsports 4, an Xbox 360 racing game. Using in-game telemetry data from more than 200,000 players and 24 million races, we characterize how players use and customize driving assists such as the trajectory line, automatic gear shifting, or assisted braking over time. We find that some of the assists are never disabled by significant player segments. Some "yoyo" players repeatedly enable and disable assists. We also present a model to predict when a player is ready to successfully disable an assist with a precision ranging from 60 to 90 percent.